A Study on Nature of Sports Injuries among Athletes of Different Age and Gender Groups in Volleyball - Dr. M.C Ghosh, Dr. Anup Mondal (International Journal of Scientific Research and Management (IJSRM), 2017)
Volleyball is the second most popular sport over the world just after the soccer.. It is played by approximately 200 million players worldwide. With more than 200 member countries in the Federation Internationale de Volley-Ball (FIVB) and about 150 million players Volleyball is a winter-season popular game in West Bengal and in Nadia in particular. The district abounds in talented players in this game but they lag behind because of their poor pecuniary condition and mal-nutrition accompanied by injuries. As it is played at a very low cost in a small room or in a small area, it has gained much popularity among the promising players of the West Bengal. The injury was search in the title of “a study on nature of sports injuries among athletes of different age and gender groups in volleyball”. For the purpose of the study 210 volleyball players of district to international was considered as the subject of the study. Each subject was provided with a questionnaire in connection with sports injuries nature, history and frequency of injury suffered by the athletes of volleyball from the analysis of the questionnaires. In the present study it was found that in senior male and female volleyball players knee and ankle ligament(sprain) injury was, male 25.% each and female 18.42% and 28.95%. Shoulder sprain, contusion or bruise and bone fracture or bone crack was 10.00% each, but in female it was 7.89% each. In under nineteen male and female volleyball players it was found that knee ligament(sprain) injury male 29.27% and female 30.%, ankle ligament(sprain) injury 21.95% and 20.00%, muscle or tendon (strain) 7.32% and 16.67% respectively. In under seventeen male and female volleyball players it was found that knee and ankle ligament(sprain) injury was male 17.14% and female 18.52%, each. In male, bone fracture or bone crack 14.29% and in female 14.81%, contusion or bruise 5.71% and 11.11% respectively. In under fourteen male and female reported maximum contusion injury 25% and 26.67%.Male reported 18.75% ankle ligament(sprain), knee ligament(sprain) and contusion or bruise injuries but in female it was 13.33%, 20% and 26.67% respectively. And finally it was concluded that Higher the age groups higher was the frequency and severity of injury